2020
DOI: 10.3390/life10040034
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite Synthesis in the Presence of Cyanide or Thiocyanate under Prebiotic Chemistry Conditions

Abstract: Magnetite is an iron oxide mineral component of primitive Earth. It is naturally synthesized in different ways, such as magma cooling as well as olivine decomposition under hydrothermal conditions. It is probable magnetite played a significant role in biogenesis. The seawater used in the current work contained high Mg2+, Ca2+ and SO42− concentrations, unlike the seawater of today that has high Na+ and Cl− concentrations. It is likely that this seawater better resembled the ion composition of the seas of the Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 57 publications
(82 reference statements)
3
8
0
Order By: Relevance
“…In addition, Samulewski et al . (2020) also observed that when magnetite was synthesized in the presence of SCN − anion, goethite was also obtained. For Fh-DW-NH 4 SCN-1 and Fh-DW-NH 4 SCN-2 samples, the (hematite, (018)) and (magnetite, (311)) peaks should be the highest intensity, but probably due to orientation, they are not (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…In addition, Samulewski et al . (2020) also observed that when magnetite was synthesized in the presence of SCN − anion, goethite was also obtained. For Fh-DW-NH 4 SCN-1 and Fh-DW-NH 4 SCN-2 samples, the (hematite, (018)) and (magnetite, (311)) peaks should be the highest intensity, but probably due to orientation, they are not (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…However, the FT-IR spectra of Fh-DW-NH 4 SCN-2, Fh-SW-NH 4 SCN-1 and Fh-DW-NH 4 SCN-1 samples showed bands at 890 cm −1 (O-H bending in plane) and 794 cm −1 (O-H bending out of the plane) which are characteristic of goethite (Table 1) (Cornell and Schwertmann, 2003). In addition, Samulewski et al (2020) also observed that when magnetite was synthesized in the presence of SCN − anion, goethite was also obtained. For Fh-DW-NH 4 SCN-1 and Fh-DW-NH 4 SCN-2 samples, the (hematite, (018)) and (magnetite, (311)) peaks should be the highest intensity, but probably due to orientation, they are not (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations